import system_of_complexes.basic /-! # The normed snake dual lemma: weak and non-weak This file proves the weak normed snake dual lemma and the normed snake dual lemma: they are the statements `weak_normed_snake_dual` and `normed_snake_dual`, respectively. The principal definitions of the concepts in this file appear in Section 4 of the blueprint. The two main results prove `is_(weak_)bounded_exact` for certain `system_of_complexes`. The Lean-definitions of these concepts appears in `system_of_complexes.basic`. Intuitively, the two predicates assert a version of exactness for a complex whose overall shape is an inequality of the form ```lean ∥res ? - (M.d ??) ?∥ ≤ const * ∥(M.d ?? ?∥ + ε. ``` (Recall that `res` is a restriction among certain complexes, `M.d` stands for a differential, `const` is a constant; the error `ε` is a non-negative real number. For the weak version, we quantify over all `0 < ε ∈ ℝ`. For the non-weak version, we use `ε = 0`.) More in detail, at the heart of the computation, is a proof of an inequality of the form ```lean ∥res m - (M.d (i - 1) i) y∥ ≤ K * (1 + K' * r₁ * r₂) * ∥(M.d i (i + 1)) m∥ + ε. ``` In the weak normed snake dual lemma, for any choice of positive `0 < ε`, we should be able to fix the parameters so that the inequality above is satisfied. In the normed snake dual lemma, we want the inequality above with `ε = 0`. As you will see, the bulk of the proof of the normed snake dual lemma recycles the proof of the weak version. The proof involves several estimations: we broke these proofs into smaller partial inequalities, for three reasons. First, it streamlines the formalization. Second, it helps Lean processing the statements, reducing processing times. Third, it allows us to us a large part of the argument for both `weak_normed_snake_dual` and `normed_snake_dual`. # Remark While following the proof, keep an eye out for how the factor `ρ = 1 + K' * r₁ * r₂` forms itself. Once the factor `ρ` is formed, we can almost treat it as a new strictly positive variable. -/ universe variables u noncomputable theory open_locale nnreal open category_theory opposite normed_add_group_hom system_of_complexes variables {M N P : system_of_complexes.{u}} {f : M ⟶ N} {g : N ⟶ P} /- I (DT) extracted this lemma to speed up the proof of `weak_normed_snake_dual`. -/ lemma ε₁_le_ε {ε ε₁ : ℝ} (hε : 0 ≤ ε) (mK : ℝ≥0) (hε₁ : ε₁ = ε / 2 * (1 + mK)⁻¹) : ε₁ ≤ ε := by { rw [hε₁, div_eq_mul_inv, mul_assoc, ← mul_inv], exact mul_le_of_le_one_right hε (inv_le_one $ nnreal.coe_le_coe.mpr $ one_le_mul one_le_two $ le_add_of_nonneg_right mK.2) } /-! First, we break off the main term `∥res m - (M.d i' i) m₁∥` into a sum of two expressions: * `∥(res (f m) : N c i) - N.d i' i (res n₁)∥`, and * `∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥`. -/ lemma norm_sub_le_split {k' c c₁ : ℝ≥0} {i i' i'' : ℕ} [hk' : fact (1 ≤ k')] [fc : fact (c ≤ c₁)] (hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) {n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m₁ : M c i'} {m : (M c₁ i)} (hm₁ : f m₁ = res n₁ - ((N.d i'' i') n₂) - nnew₁) : ∥res m - (M.d i' i) m₁∥ ≤ ∥(res (f m) : N c i) - N.d i' i (res n₁)∥ + ∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ := calc ∥res m - (M.d i' i) m₁∥ = ∥f (res m - (M.d i' i) m₁)∥ : (hfnorm _ _ _).symm ... = ∥res (f m) - (N.d i' i (res n₁) - N.d i' i ((N.d i'' i') n₂ + nnew₁))∥ : by rw [hom_apply, _root_.map_sub, ←hom_apply, ←hom_apply, ←res_apply, ←d_apply, hm₁, sub_sub, _root_.map_sub] ... = ∥(res (f m) - N.d i' i (res n₁)) + N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : by rw [sub_eq_add_neg, neg_sub, sub_eq_neg_add, ← add_assoc, ← sub_eq_add_neg] ... ≤ ∥res (f m) - N.d i' i (res n₁)∥ + ∥N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : norm_add_le _ _ /-! We then massage the left-hand side. The proof of this lemma is deceptively simple, since there is a lot of typeclass work happening in the background. In particular, the `c` in the sea of underscores of the second line is crucial for the *previous* line to compile. (The hypothesis `(hN_adm : N.admissible)` is only used via `(hN_adm.res_norm_noninc _ c _ _ _)`, producing the inequality `(dis : ∥(res (res (f m) - (N.d i' i) n₁) : N c i)∥ ≤ ∥res (f m) - (N.d i' i) n₁∥)`.) -/ lemma norm_sub_le_mul_norm_add_lhs {k' K c c₁ : ℝ≥0} {ε₁ : ℝ} {i i' : ℕ} [hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] [fc : fact (c ≤ c₁)] {n₁ : N (k' * c) i'} {m : (M c₁ i)} (hN_adm : N.admissible) (hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) : ∥(res (f m) : N c i) - N.d i' i (res n₁)∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁ := calc ∥(res (f m) : N c i) - N.d i' i (res n₁)∥ = ∥res (res (f m) - (N.d i' i) n₁)∥ : by rw [_root_.map_sub, d_res, ← res_res] ... ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁ : trans (hN_adm.res_norm_noninc _ c _ _ _) hn₁ /-! And we also massage the right-hand side. Here, the factor `K' * r₁ * r₂` appears. (The hypothesis `(hN_adm : N.admissible)` is only used via `(hN_adm.d_norm_noninc _ _ i' i nnew₁)`, producing the inequality `(dis : ∥(N.d i' i) nnew₁∥ ≤ ∥nnew₁∥)`.) -/ lemma norm_sub_le_mul_norm_add_rhs {k' K K' r₁ r₂ c c₁ : ℝ≥0} {ε₁ ε₂ : ℝ} {i i' i'' : ℕ} (hii' : i' + 1 = i) [hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] (hgnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ ↑r₁ * ∥x∥) {n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m : (M c₁ i)} (hN_adm : N.admissible) (hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) (hp₂ : ∥res (g n₁) - (P.d i'' i') (g n₂)∥ ≤ K' * ∥(P.d i' (i' + 1)) (g n₁)∥ + ε₂) (hnormnnew₁ : ∥nnew₁∥ ≤ r₂ * ∥g (res n₁ - ((N.d i'' i') n₂))∥) (hfm : ∥g ((N.d i' i) n₁)∥ = ∥g (res (f m) - (N.d i' i) n₁)∥) : ∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ ≤ K * K' * r₁ * r₂ * ∥(N.d i (i+1)) (f m)∥ + K' * r₁ * r₂ * ε₁ + r₂ * ε₂ := calc ∥(N.d i' i ((N.d i'' i') n₂ + nnew₁) : N c i)∥ = ∥N.d i' i nnew₁∥ : by simp only [map_add, zero_add, d_d] ... ≤ r₂ * ∥g (res n₁ - (N.d i'' i') n₂)∥ : trans (hN_adm.d_norm_noninc _ _ i' i nnew₁) hnormnnew₁ ... = r₂ * ∥res (g n₁) - P.d i'' i' (g n₂)∥ : by rw [hom_apply, _root_.map_sub, ←hom_apply, ←hom_apply, ←res_apply _ _ g, ←d_apply] ... ≤ r₂ * (K' * ∥P.d i' (i'+1) (g n₁)∥ + ε₂) : mul_le_mul_of_nonneg_left hp₂ r₂.coe_nonneg ... = r₂ * (K' * ∥g (res (f m) - N.d i' i n₁)∥ + ε₂) : by rw [d_apply _ _ g _, hii', hfm] ... ≤ r₂ * (K' * (r₁ * ∥res (f m) - N.d i' i n₁∥) + ε₂) : mul_le_mul_of_nonneg_left (add_le_add_right (mul_le_mul_of_nonneg_left (hgnorm _ _ _) K'.coe_nonneg) _) $ r₂.coe_nonneg ... = r₂ * (K' * r₁ * ∥res (f m) - N.d i' i n₁∥ + ε₂) : by rw mul_assoc ... ≤ r₂ * (K' * r₁ * (K * ∥(N.d i (i+1)) (f m)∥ + ε₁) + ε₂) : mul_le_mul_of_nonneg_left (add_le_add_right (mul_le_mul_of_nonneg_left hn₁ $ mul_nonneg K'.coe_nonneg r₁.coe_nonneg) _) r₂.coe_nonneg ... = _ : by ring /-! We collect the inequalities obtained so far: * use `norm_sub_le_split` to split the norm into a sum of two terme; * apply `norm_sub_le_mul_norm_add_lhs` to the left-hand-side; * apply `norm_sub_le_mul_norm_add_rhs` to the right-hand-side. The rest is simple manipulations of real numbers. -/ lemma norm_sub_le_mul_norm_add {k' K K' r₁ r₂ c c₁ : ℝ≥0} {ε ε₁ ε₂ : ℝ} {i i' i'' : ℕ} (hii' : i' + 1 = i) [hk' : fact (1 ≤ k')] [fc₁ : fact (k' * c ≤ c₁)] [fc : fact (c ≤ c₁)] (hN_adm : N.admissible) (hgnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ ↑r₁ * ∥x∥) (hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) {n₁ : N (k' * c) i'} {n₂ : N c i''} {nnew₁ : N c i'} {m₁ : M c i'} {m : (M c₁ i)} (hmulε₁ : ε₁ * (1 + K' * r₁ * r₂) = ε / 2) (hle : (r₂ : ℝ) * ε₂ ≤ ε / 2) (hn₁ : ∥res (f m) - (N.d i' i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) (hp₂ : ∥res (g n₁) - (P.d i'' i') (g n₂)∥ ≤ K' * ∥(P.d i' (i' + 1)) (g n₁)∥ + ε₂) (hnormnnew₁ : ∥nnew₁∥ ≤ r₂ * ∥g (res n₁ - ((N.d i'' i') n₂))∥) (hm₁ : f m₁ = res n₁ - ((N.d i'' i') n₂) - nnew₁) (hfm : ∥g ((N.d i' i) n₁)∥ = ∥g (res (f m) - (N.d i' i) n₁)∥) : ∥res m - (M.d i' i) m₁∥ ≤ (K + r₁ * r₂ * K * K') * ∥(M.d i (i + 1)) m∥ + ε := calc ∥res m - (M.d i' i) m₁∥ ≤ ∥res (f m) - N.d i' i (res n₁)∥ + ∥N.d i' i ((N.d i'' i') n₂ + nnew₁)∥ : norm_sub_le_split hfnorm hm₁ ... ≤ (K * ∥(N.d i (i + 1)) (f m)∥ + ε₁) + (K * K' * r₁ * r₂ * ∥(N.d i (i+1)) (f m)∥ + K' * r₁ * r₂ * ε₁ + r₂ * ε₂) : add_le_add (norm_sub_le_mul_norm_add_lhs hN_adm hn₁) (norm_sub_le_mul_norm_add_rhs hii' hgnorm hN_adm hn₁ hp₂ hnormnnew₁ hfm) ... = (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε₁ * (1 + K' * r₁ * r₂) + r₂ * ε₂ : by ring ... = (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε / 2 + r₂ * ε₂ : congr_arg (λ e, (↑K + ↑r₁ * ↑r₂ * ↑K * ↑K') * ∥(N.d i (i + 1)) (f m)∥ + e + ↑r₂ * ε₂) hmulε₁ ... ≤ (K + r₁ * r₂ * K * K') * ∥N.d i (i+1) (f m)∥ + ε / 2 + ε / 2 : add_le_add_left hle _ ... = (K + r₁ * r₂ * K * K') * ∥(M.d i (i+1)) m∥ + ε : by rw [add_assoc, add_halves', d_apply, hom_apply, hfnorm] /-! We shall apply this lemma with `ρ = K + r₁ * r₂ * K * K' = K * (1 + K' * r₁ * r₂)`. -/ lemma exists_norm_sub_le_mul_add {k k' c ρ : ℝ≥0} {i : ℕ} [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] (hM_adm : M.admissible) (ex_le : (∀ (m : (M (k * (k' * c)) i)) (ε : ℝ), 0 < ε → (∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), ∥res m - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i (i + 1)) m∥ + ε))) {m₁ : (M (k * k' * c) i)} {ε : ℝ} (hε : 0 < ε) : ∃ (i₀ j : ℕ) (hi₀ : i₀ = i - 1) (hj : i + 1 = j) (y : (M c i₀)), ∥res m₁ - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i j) m₁∥ + ε := begin haveI : fact (k * (k' * c) ≤ k * k' * c) := { out := (mul_assoc _ _ _).symm.le }, rcases ex_le (res m₁) ε hε with ⟨i₀, rfl, y, hy⟩, rw [res_res, d_res] at hy, refine ⟨i - 1, _, rfl, rfl, _⟩, refine ⟨y, hy.trans (add_le_add_right (mul_le_mul_of_nonneg_left _ ρ.2) ε)⟩, exact hM_adm.res_norm_noninc _ _ _ _ _, end /-! This argument proves the main inequality in the case where the indices are `0` or `1`. -/ lemma norm_sub_le_mul_mul_norm_add {M N : system_of_complexes} {f : M ⟶ N} {k k' K c : ℝ≥0} (mK : ℝ≥0) {ε ε₁ : ℝ} {m : M (k * (k' * c)) 0} {n₁ : N (k' * c) 0} {m₁ : M c 0} (ee1 : ε₁ ≤ ε) [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] (hfnorm : ∀ (c : ℝ≥0) (i : ℕ) (x : (M c i)), ∥(f.apply) x∥ = ∥x∥) (inadm : ∥((res (res m : (M (k' * c) 0))) : (M c 0))∥ ≤ ∥(res m : (M (k' * c) 0))∥ ) (hn₁ : ∥res (f m) - (N.d 0 0) n₁∥ ≤ ↑K * ∥(N.d 0 (0 + 1)) (f m)∥ + ε₁) : ∥res m - (M.d 0 0) m₁∥ ≤ (K * (1 + mK)) * ∥(M.d 0 (0 + 1)) m∥ + ε := begin simp only [d_self_apply, sub_zero, nnreal.coe_add, nnreal.coe_mul] at hn₁ ⊢, rw [res_apply, hom_apply f (res m), hfnorm] at hn₁, have new : fact (c ≤ k' * c) := { out := le_mul_of_one_le_left c.2 hk'.out }, rw ←res_res _ _ _ new, refine le_trans inadm (le_trans hn₁ _), rw [d_apply, hom_apply f _, hfnorm], refine add_le_add _ ee1, rw mul_assoc, refine (mul_le_mul_of_nonneg_left _ K.2), exact le_mul_of_one_le_left (norm_nonneg _) (le_add_of_nonneg_right mK.2), end /-! Note that `ε = 0` is allowed. Indeed, the weak normed snake dual lemma uses `0 ≤ ε`, while the normed snake dual lemma uses `ε = 0`. -/ lemma exist_norm_sub_le_mul_norm_add {k k' K K' r₁ r₂ c₀ c : ℝ≥0} {a i : ℕ} {ε : ℝ} (hε : 0 ≤ ε) [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] (hN_adm : N.admissible) (hgnrm : ∀ (c : ℝ≥0) (i : ℕ) (x : (N c i)), ∥g x∥ ≤ r₁ * ∥x∥) (Hg : ∀ (c : ℝ≥0) [_inst_1 : fact (c₀ ≤ c)] (i : ℕ), i ≤ a + 1 + 1 → ∀ (y : (P c i)), ∃ (x : (N c i)), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) (hg : ∀ (c : ℝ≥0) (i : ℕ), (range f.apply : add_subgroup (N c i)) = ker g.apply) (hf : ∀ (c : ℝ≥0) (i : ℕ), (isometry (f.apply : M c i ⟶ N c i) : _)) (hc : fact (c₀ ≤ c)) (hi : i ≤ a) {m : M (k * (k' * c)) i} {n₁ : N (k' * c) (i - 1)} (hn₁ : ∥res (f m) - (N.d (i - 1) i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + ε / 2 * (1 + K' * r₁ * r₂)⁻¹) (Hi' : i - 1 ≤ a + 1) (p₂ : P c (i - 1 - 1)) (hp₂ : ∥res (g n₁) - (P.d (i - 1 - 1) (i - 1)) p₂∥ ≤ K' * ∥(P.d (i - 1) (i - 1 + 1)) (g n₁)∥ + ite (r₂ = 0) 1 (ε / 2 * (r₂)⁻¹)) : ∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), ∥res m - (M.d i₀ i) y∥ ≤ (K + r₁ * r₂ * K * K') * ∥(M.d i (i + 1)) m∥ + ε := begin obtain ⟨n₂, rfl, hnormn₂⟩ := Hg c (i - 1 - 1) (trans (nat.pred_le _) (trans Hi' (nat.le_succ _))) p₂, let n₁' := N.d (i - 1 - 1) (i - 1) n₂, obtain ⟨nnew₁, hnnew₁, hnrmnew₁⟩ := Hg c (i - 1) (trans Hi' a.succ.le_succ) (g (res n₁ - n₁')), have hker : (res n₁ - n₁') - nnew₁ ∈ g.apply.ker, { rw [mem_ker, _root_.map_sub, sub_eq_zero, ←hom_apply, ←hom_apply, hnnew₁] }, rw ←hg at hker, obtain ⟨m₁, hm₁ : f m₁ = res n₁ - n₁' - nnew₁⟩ := (mem_range _ _).1 hker, refine ⟨i - 1, rfl, m₁, _⟩, have hfnrm : ∀ c i (x : M c i), ∥f.apply x∥ = ∥x∥ := λ c i x, (add_monoid_hom_class.isometry_iff_norm _).1 (hf c i) x, by_cases hizero : i = 0, { subst hizero, convert norm_sub_le_mul_mul_norm_add (K' * r₁ * r₂) _ hfnrm _ hn₁, { norm_cast, ring }, { exact ε₁_le_ε hε (K' * r₁ * r₂) rfl }, { exact (admissible_of_isometry hN_adm hf).res_norm_noninc _ _ _ _ _ } }, { refine norm_sub_le_mul_norm_add _ hN_adm hgnrm hfnrm _ _ hn₁ hp₂ hnrmnew₁ hm₁ _, { exact nat.succ_pred_eq_of_pos (nat.pos_of_ne_zero hizero) }, { rw inv_mul_cancel_right₀, exact ne_of_gt (add_pos_of_pos_of_nonneg zero_lt_one (zero_le (K' * r₁ * r₂))) }, { by_cases H : r₂ = 0, { simp only [H, nnreal.coe_zero, if_true, zero_mul, (div_nonneg hε zero_le_two)] }, { simp only [H, nnreal.coe_eq_zero, if_false, mul_comm, mul_inv_cancel_left₀ (nnreal.coe_ne_zero.mpr H)] } }, { have : f (res m : M (k' * c) i) ∈ f.apply.range, { rw mem_range, exact ⟨res m, rfl⟩ }, rw [hg, mem_ker] at this, rw [hom_apply g (res (f m) - (N.d (i - 1) i) n₁), res_apply, _root_.map_sub, this, zero_sub, norm_neg, ←hom_apply] } } end /-! We apply this lemma with `ρ = K + r₁ * r₂ * K * K'`. -/ lemma exists_norm_sub_le_mul {M : system_of_complexes} {k k' c ρ : ℝ≥0} {i : ℕ} [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] (hM_adm : M.admissible) (ex_le : (∀ (m : (M (k * (k' * c)) i)), (∃ (i₀ : ℕ) (hi₀ : i₀ = i - 1) (y : (M c i₀)), ∥res m - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i (i + 1)) m∥))) (m₁ : (M (k * k' * c) i)) : ∃ (i₀ j : ℕ) (hi₀ : i₀ = i - 1) (hj : i + 1 = j) (y : (M c i₀)), ∥res m₁ - (M.d i₀ i) y∥ ≤ ↑ρ * ∥(M.d i j) m₁∥ := begin haveI : fact (k * (k' * c) ≤ k * k' * c) := { out := (mul_assoc _ _ _).symm.le }, rcases ex_le (res m₁) with ⟨i₀, rfl, y, hy⟩, rw [res_res, d_res] at hy, refine ⟨i - 1, _, rfl, rfl, _⟩, refine ⟨y, hy.trans (mul_le_mul_of_nonneg_left _ ρ.2)⟩, exact hM_adm.res_norm_noninc _ _ _ _ _, end variables (M N P f g) /-! Finally, we state and prove the weak normed snake dual lemma. -/ lemma weak_normed_snake_dual (k k' K K' r₁ r₂ : ℝ≥0) [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] {a : ℕ} {c₀ : ℝ≥0} (hN : N.is_weak_bounded_exact k K (a + 1) c₀) (hP : P.is_weak_bounded_exact k' K' (a + 1) c₀) (hN_adm : N.admissible) (hgnrm : ∀ c i (x : N c i), ∥g x∥ ≤ r₁ * ∥x∥) (Hg : ∀ (c : ℝ≥0) [fact (c₀ ≤ c)] (i : ℕ) (hi : i ≤ a + 1 + 1) (y : P c i), ∃ (x : N c i), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) (hg : ∀ c i, (f.apply : M c i ⟶ N c i).range = g.apply.ker) (hf : ∀ c i, @isometry (M c i) (N c i) _ _ f.apply) : M.is_weak_bounded_exact (k * k') (K + r₁ * r₂ * K * K') a c₀ := begin introsI c hc i hi, apply exists_norm_sub_le_mul_add (admissible_of_isometry hN_adm hf), intros m ε hε, have hε₁ : 0 < ε / 2 * (1 + K' * r₁ * r₂)⁻¹ := mul_pos (half_pos hε) (inv_pos.2 $ add_pos_of_pos_of_nonneg zero_lt_one ((K' * r₁ * r₂).coe_nonneg)), obtain ⟨_, _, rfl, rfl, n₁, hn₁⟩ := hN _ ⟨hc.out.trans $ le_mul_of_one_le_left' hk'.out⟩ _ (trans hi a.le_succ) (f m) _ hε₁, have Hi' : i - 1 ≤ a + 1 := trans i.pred_le (trans hi a.le_succ), obtain ⟨_, _, rfl, rfl, p₂, hp₂⟩ := hP _ hc _ Hi' (g n₁) (if (r₂ : ℝ) = 0 then 1 else (ε / 2) * r₂⁻¹) _, { simp_rw [nnreal.coe_eq_zero r₂] at hp₂, apply exist_norm_sub_le_mul_norm_add hε.le hN_adm hgnrm Hg hg hf hc hi hn₁ Hi' p₂, convert hp₂, }, { by_cases H : r₂ = 0, { simp only [H, zero_lt_one, if_true, eq_self_iff_true, nnreal.coe_eq_zero] }, { simp only [H, nnreal.coe_eq_zero, if_false], exact mul_pos (half_pos hε) (inv_pos.2 (nnreal.coe_pos.2 (zero_lt_iff.2 H))) } } end /-! And also the normed snake dual lemma. -/ lemma normed_snake_dual {k k' K K' r₁ r₂ : ℝ≥0} [hk : fact (1 ≤ k)] [hk' : fact (1 ≤ k')] {a : ℕ} {c₀ : ℝ≥0} (hN : N.is_bounded_exact k K (a + 1) c₀) (hP : P.is_bounded_exact k' K' (a + 1) c₀) (hN_adm : N.admissible) (hgnorm : ∀ c i (x : N c i), ∥g x∥ ≤ r₁ * ∥x∥) (Hg : ∀ (c : ℝ≥0) [fact (c₀ ≤ c)] (i : ℕ) (hi : i ≤ a + 1 + 1) (y : P c i), ∃ (x : N c i), g x = y ∧ ∥x∥ ≤ r₂ * ∥y∥) (hg : ∀ c i, (f.apply : M c i ⟶ N c i).range = g.apply.ker) (hf : ∀ c i, @isometry (M c i) (N c i) _ _ f.apply) : M.is_bounded_exact (k * k') (K + r₁ * r₂ * K * K') a c₀ := begin introsI c hc i hi, refine exists_norm_sub_le_mul (admissible_of_isometry hN_adm hf) _, intro m, obtain ⟨_, _, rfl, rfl, n₁, hn₁⟩ := hN _ ⟨hc.out.trans $ le_mul_of_one_le_left' hk'.out⟩ _ (trans hi a.le_succ) (f m), have Hi' : (i - 1) ≤ a + 1 := trans i.pred_le (trans hi a.le_succ), obtain ⟨_, _, rfl, rfl, p₂, hp₂⟩ := hP _ hc _ Hi' (g n₁), rw ← add_zero (_ * ∥_∥) at ⊢, have hn₁₁ : ∥res (f m) - (N.d (i - 1) i) n₁∥ ≤ K * ∥(N.d i (i + 1)) (f m)∥ + 0 / 2 * (1 + K' * r₁ * r₂)⁻¹, rwa [zero_div, zero_mul, add_zero], obtain F := exist_norm_sub_le_mul_norm_add rfl.le hN_adm hgnorm Hg hg hf hc hi hn₁₁ Hi' p₂, by_cases hr : r₂ = 0, { subst hr, simp at ⊢ F, exact F (trans hp₂ (le_add_of_nonneg_right zero_le_one)) }, { exact F (by { convert hp₂, simp [hr] } ) } end